DISTRIBUTION OF CERCOSPORA ORYZAE, THE FUNGUS CAUSING CERCOSPORA LEAF SPOT OR NARROW BROWN LEAF SPOT IN SOUTHERN BENIN (ADVANTAGES AND CONSTRAINTS OF RICE PRODUCTION) - SOURA, HERVE; GNANCADJA, LEOPOLD SIMPLE; KOITA, KADIDJATOU; GNACADJA, CLAUDE (My University, 2018)
Southern Benin is full of potential rice growing because of its climate, pedology. Three types of rice cultivation are practiced, the most dominant lowland rice growing, rainfed rice and irrigated rice. Collections were carried out in six departments of southern Benin, thirteen villages and nine municipalities were prospected. Several fungal diseases have been observed in southern Benin at different stages of the rice development cycle. A predominance of cercospora in six villages (Docomey, Gative, Matekpo, Zoungo, Aizè, Kpodji) was recorded, curvularia observed in three villages (Gative, Matekpo, Houeli-Gaba), blast disease observed in five villages (Docomey, Matekpo, Kpodji, Zoungo, Aizè). No symptoms of fungal disease were observed in the rice fields of five villages: Awokpa, Kode- Agu, Gouti, Odja-Igbagi, Ouinhi. The IR841 is the most cultivated variety. Producers as a whole did not know how to differentiate fungal diseases from other diseases (bacterial, viral) of rice. They recognize for some the symptoms of blast. The necrotic appearance and color of brown spots allow growers to identify certain leaf diseases. The symptoms of fungal diseases were observed in 8 of the 13 sites surveyed at different stages of the rice development cycle. Cercospora leaf spot disease caused by Cercospora oryzae is observed from the panicle phase to maturity. Producers have a lack of knowledge of Cercosporiosis, which can cause losses ranging from 40% to 60% of production. The rice sector in southern Benin will be better able if the actors could benefit from training, supervision in the direction of plant protection.
Keywords: Rice; Oryzae; Pathogen; Fungus; Cercospora; distribution.